Brain anatomy of a clonal fish, the Amazon Molly (Poecilia formosa): effects of early-life environment - Hayo G. Nadema; Tyler J. Reich; Eline J. E. Weenink; Debbie Cunningham; Elvis Wong; Ingo Schlupp; Alexander Kotrschal (Evolutionary Ecology, 2025)
During ontogeny, environmental factors can shape trait development and resource allocation to aid survival, reflecting adaptive plasticity. This may include differential investment in brain regions in response to cognitive challenges. Especially the brain anatomy of fish seems to respond readily to biotic and abiotic factors. However, we currently lack sufficient data to determine the extent to which such changes are consistent across species. To extend the phylogenetic breadth in this endeavour, we studied how brain anatomy of Amazon mollies ( Poecilia formosa ) responds to the presence or absence of physical enrichment and/or visual neighbours. The Amazon molly is a clonal species and genetically highly uniform, so that differences in brain anatomy of individuals from the same clonal lineage are most likely due to the environmental conditions provided, rather than inherent genetic differences. We quantified brain anatomy by determining the volumes of six main brain regions (olfactory bulb; telencephalon; optic tectum; cerebellum; dorsal medulla; hypothalamus) and overall brain size. While brain anatomy was overall unaffected by the visual presence of a conspecific, we found that the cerebellum was larger in animals reared in an environmentally complex habitat. Our results corroborate the idea that use of certain cognitive domains fosters enlargement in the region governing those.